The Tour de France, also possible for mortals? A comparison of a recreational and a World Tour cyclist - Barranco-Gil, D.; Muriel, X.; Lucia, A.; Joyner, M. J.; DeSouza, C. A.; Valenzuela, P. L. (Journal of Applied Physiology, 2024)
Cycling Grand Tours are arguably the epitome of strenuous endurance exercise, and they have been reported to represent the ceiling of sustained energy expenditure for humans. It remains unknown, however, if an average recreational athlete could endure such an event. Through the analysis of power output (PO), we compared data from the 2023 Tour de France (21 stages, total distance = 3,405 km, elevation gain = 51,815 m) in a recreational (male, age = 58 yr; height = 191 cm; body mass = 96.1 kg; estimated maximum oxygen uptake = 45.4 mL·kg-1·min-1) and a sex-matched professional (World-Tour) cyclist (28 yr; 180 cm; 67.0 kg; 80.5 mL·kg-1·min-1). The recreational and professional cyclist completed the event in 191 and 87 h, respectively (average PO of 1.50 and 3.45 W·kg-1), with the latter spending a greater proportion of time in high-intensity zones. The recreational cyclist showed an estimated total daily energy expenditure (TDEE) of 35.9 MJ [or 8,580 kcal, or ~4.3× his daily basal metabolic rate (BMR)], whereas lower absolute values were estimated for the professional cyclist (29.7 MJ, 7,098 kcal, ~3.8× his BMR). Despite such high TDEE values, both individuals lost minimal body mass during the event (0-2 kg). The present report therefore suggests that, partly due to differences in exercise intensity and duration, not only professional cyclists but also recreational athletes can reach currently known ceilings of TDEE for humans.